Anthropogenic Nitrogen‐Induced Changes in Seasonal Carbonate Dynamics in a Productive Coastal Environment. Issue 17 (4th September 2020) - Kim, Ja‐Myung; Lee, Kitack; Han, In‐Seong; Lee, Joon‐Soo; Choi, Yang‐Ho; Lee, Ju Hyeon; Moon, Ji‐Young
Abstract: We estimated the seasonal extremes in pH and the aragonite saturation state (Ωarag ) for the Yellow Sea over the past 30 years using recent (2015–2018) carbonate data sets, along with historical data sets of surface N and bottom water dissolved O2 concentrations. The rate of increase in surface N was assumed to determine the postbloom surface dissolved inorganic C concentration resulting from the complete utilization of N by phytoplankton, while the decrease in bottom water O2 was assumed to reflect the prebloom surface C, as a consequence of C‐rich bottom water (resulting from the oxidation of greater amounts of organic matter transported from the surface) being brought to the surface. With the increasing loads of anthropogenic N, the net community metabolism (an increase in organic matter production at the surface and subsequent remineralization at the seafloor) has lowered the seasonal amplitude of pH by 0.14 but increased the amplitude of Ωarag by 0.8. Plain Language Summary: As little is known about changes in the seasonal amplitudes of ocean pH and the aragonite saturation state (Ωarag ), we evaluated their seasonal dynamics using carbonate parameter data for the Yellow Sea (2015–2018). We extrapolated the measured seasonal amplitudes of pH and Ωarag backward in time for the past 30 years, based on data sets of surface nitrate (N) and near‐bottom O2 concentrations. The increased surface N concentration was assumed to be translated into phytoplankton biomass (indicating the complete consumption of N by phytoplankton) and thus determined the postbloom surface dissolved inorganic C condition (the August values). The oxidation of resulting organic matter was assumed to set the rate of decrease in the bottom water O2 concentration; the C‐rich bottom water subsequently reached the surface by wind‐driven turbulence and dictated the prebloom surface C conditions (the April values). Our study shows that the N‐driven net community metabolism resulted in the increase in photosynthesis and respiration and decreased the seasonal pH amplitude by 0.14 but increased the seasonal Ωarag amplitude by 0.8. We conclude that the net community metabolism is a major driver of change in the seasonal amplitude of carbonate parameters in the coastal oceans receiving increasing loads of anthropogenic N. Key Points: N‐driven net community metabolism had dual effects on coastal acidification: lowering the seasonal pH amplitude and enhancing Ωarag amplitude Net community metabolism was a key driver of change in the seasonal amplitude of pH and Ωarag in the Yellow Sea